Polymer Brush-Functionalized Chitosan Hydrogels as Antifouling Implant Coatings - Buzzacchera, Irene; Vorobii, Mariia; Kostina, Nina Yu; de Los Santos Pereira, Andres; Riedel, Tomáš; Bruns, Michael; Ogieglo, Wojciech; Möller, Martin; Wilson, Christopher J; Rodriguez-Emmenegger, Cesar (Biomacromolecules, 2017)
Implantable sensor devices require coatings that efficiently interface with the tissue environment to mediate biochemical analysis. In this regard, bioinspired polymer hydrogels offer an attractive and abundant source of coating materials. However, upon implantation these materials generally elicit inflammation and the foreign body reaction as a consequence of protein fouling on their surface and concomitant poor hemocompatibility. In this report we investigate a strategy to endow chitosan hydrogel coatings with antifouling properties by the grafting of polymer brushes in a "grafting-from" approach. Chitosan coatings were functionalized with polymer brushes of oligo(ethylene glycol) methyl ether methacrylate and 2-hydroxyethyl methacrylate using photoinduced single electron transfer living radical polymerization and the surfaces were thoroughly characterized by XPS, AFM, water contact angle goniometry, and in situ ellipsometry. The antifouling properties of these new bioinspired hydrogel-brush coatings were investigated by surface plasmon resonance. The influence of the modifications to the chitosan on hemocompatibility was assessed by contacting the surfaces with platelets and leukocytes. The coatings were hydrophilic and reached a thickness of up to 180 nm within 30 min of polymerization. The functionalization of the surface with polymer brushes significantly reduced the protein fouling and eliminated platelet activation and leukocyte adhesion. This methodology offers a facile route to functionalizing implantable sensor systems with antifouling coatings that improve hemocompatibility and pave the way for enhanced device integration in tissue.
Keywords: aktivace trombocytů; Platelet Activation; Methacrylates; primární buněčná kultura; Coated Materials, Biocompatible; methakryláty; Free Radicals; trombocyty; Polyethylene Glycols; buněčná adheze; biokompatibilní potahované materiály; lidé; chitosan; Hydrogels; Cell Adhesion; Polymerization; Chitosan; Biosensing Techniques; Blood Platelets; leukocyty; polyethylenglykoly; hydrogely; Leukocytes; Primary Cell Culture; biosenzitivní techniky; polymerizace; implantabilní infuzní pumpy; Infusion Pumps, Implantable; volné radikály; Humans